2012
DOI: 10.1016/j.bbr.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Intra-amygdala inhibition of ERK1/2 potentiates the discriminative stimulus effects of alcohol

Abstract: Extracellular signal-regulated kinase (ERK1/2) has been implicated in modulating drug seeking behavior and is a target of alcohol and other drugs of abuse. Given that the discriminative stimulus (subjective/interoceptive) effects of drugs are determinants of abuse liability and can influence drug seeking behavior, we examined the role of ERK1/2 in modulating the discriminative stimulus effects of alcohol. Using drug discrimination procedures, rats were trained to discriminate a moderate intragastric (IG) alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…This interpretation points to ERK1/2 activation as a potential cue for satiety or subjective intoxication. However, ERK1/2 inhibition in the amygdala increases the discriminative stimulus effects of a low dose of alcohol (Besheer et al, 2012) and is without effect in accumbens, which suggests the potential importance of other brain regions detected in this study such as the prefrontal cortex. Further evaluation of ERK1/2 activity in specific brain regions will clarify its potential role as a termination signal in alcohol drinking.…”
Section: Discussionmentioning
confidence: 64%
“…This interpretation points to ERK1/2 activation as a potential cue for satiety or subjective intoxication. However, ERK1/2 inhibition in the amygdala increases the discriminative stimulus effects of a low dose of alcohol (Besheer et al, 2012) and is without effect in accumbens, which suggests the potential importance of other brain regions detected in this study such as the prefrontal cortex. Further evaluation of ERK1/2 activity in specific brain regions will clarify its potential role as a termination signal in alcohol drinking.…”
Section: Discussionmentioning
confidence: 64%
“…Rats were trained using the same behavioral chambers and procedures as previous studies from this laboratory (Besheer et al 2012; Besheer et al 2014; Besheer et al 2009). Briefly, immediately following intragastric gavage (IG) administration of alcohol (1 g/kg) or water rats were placed in the chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Besheer et al . have shown that alcohol discrimination is co-regulated by mGluR5 in the NAc and the mGluR2/3 in the amygdala 7073 and that inhibition of MEK/ERK(1/2) in the amygdala, but not NAc, potentiates the effects of a low alcohol dose 74 . Recent work with stress hormone corticosterone links both mGluR5 and mGluR2/3 in the sensitivity to alcohol 75, 76 , suggesting a role for neuropeptide modulation of glutamatergic circuits.…”
Section: Low-level Drinkingmentioning
confidence: 99%